Design and synthesis of 8-nitroquinoline azine D-π-A module chemosensors: Fluorogenic onsite detection of sarin gas mimic- DCP - Sentamil Selvi Ramasamy; Kaviyarasu Adhigaman; Vandana Nandakumar; Akilesh Muralidharan; Shankar Ramasamy; Suresh Thangaraj (Talanta Open, 2025)
Organophosphorus (OP) chemical warfare agents are highly toxic and directly interrupts the acetylcholine esterase (AChE) enzyme activity in the central nervous system while exposed to those lethal substances. Detection of OP agents is challenging one and existing analytical methods are also having limitations and tedious operating procedures. In this context, we designed two ICT based 8-nitro substituted quinoline unsymmetrical azine sensors (NQH and NQH-1) for the detection of sarin mimic diethylchlorophosphate (DCP) nerve agent. The developed sensors are shown significant orange region emissive responses to DCP molecule in “TURN ON” manner with reliable red shifts. The limit of detection for the probes NQH and NQH-1 were in micromolar level found to be 1.5 and 3.2 µM respectively. The consequent mechanistic pathway proposed for the sensing systems are PET combined with ICT for NQH, while the NQH-1 system functions through ESIPT coupled with ICT processes. The proposed mechanistic gateway further elucidated through 1H NMR, 31P NMR titrations in addition to the dynamics of DFT. Notably, the proposed D-π-A module chemosensors have good fluorescent module for instant field level recognition of nerve agents (surrogates). The significance of the research found in the sensing platform has been achieved by the fabrication of cotton swab and paper disc kits for the real time analysis.